Analisis Kebijakan Fiskal Pasca Pandemi Covid-19 Studi Kasus Indonesia - Latifah, Leni Lenza; Rosyadi, Slamet (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
After the Covid-19 outbreak, there was a decline in various sectors in Indonesia, including the economic sector. Various efforts have been made to restore stability to the Indonesian economy. Fiscal policy is one of the government's efforts to restore the economy. Fiscal policy will have a significant impact on the Indonesian economy and bring major changes to Indonesia's development system. This fiscal policy is mainly determined by the government's involvement in economic activities. This is based on the government's role in achieving a prosperous society, one of which is the use of appropriate policy instruments. The research method uses qualitative research using a literature review method by collaborating with various literature related to Fiscal Policy in Indonesia. The data sources in this research are secondary data in the form of journals, articles, books and other relevant references. The results show that the government made a strategy by implementing fiscal policy on state revenues and expenditures with the aim of restoring the country's economy and stabilizing the community economy. However, with the impressive growth rate of the Indonesian economy, the government also needs to review and pay attention again and ensure that the assistance provided by the government can be allocated on target. And there is also a need for innovation in fiscal policy regulations that can create a new balance between business actors, including entrepreneurs, society and government. Keywords: Fiscal Policy, Covid 19 Pandemic